2020
DOI: 10.3389/fimmu.2020.01335
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantification of Histone H4 Citrullination in Early NETosis With Image Flow Cytometry Version 4

Abstract: Neutrophil extracellular traps (NETs) formation has been implicated in an increasing number of infectious and non-infectious pathologies. NETosis is a tightly regulated process; the end-stage and read-out is the formation of DNA strands extruded from the nuclei, and traditionally assessed by fluorescence microscopy. Since NETosis has emerged as a possible biomarker of the inflammatory process, there is a need for less time-consuming, consistent, and quantitative approaches to improve its application in clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…In addition to CitH3, the citrullination of H1.0, H1.4, H1.5 and H2B was also detected in RA NET [28]. Because of its quantifiable response to all kinds of stimuli of NETs, CitH4 was identified as an index of early NETs [129]. In conclusion, both core histones (H2, H3 and H4) and linker histone H1 present citrullination in NETs.…”
Section: Nets and Tumorsmentioning
confidence: 81%
“…In addition to CitH3, the citrullination of H1.0, H1.4, H1.5 and H2B was also detected in RA NET [28]. Because of its quantifiable response to all kinds of stimuli of NETs, CitH4 was identified as an index of early NETs [129]. In conclusion, both core histones (H2, H3 and H4) and linker histone H1 present citrullination in NETs.…”
Section: Nets and Tumorsmentioning
confidence: 81%
“…In a recent study, abnormal coagulation (confirmed by D-dimer concentration) [ 56 , 57 ] and NETosis ( i.e. , cfDNA, NET, MPO activity, and NE) [ [58] , [59] , [60] , [61] ] were also confirmed in the SARS-CoV-2 ICU patient plasma, and the correlation between elevated histone H4 level and blood coagulation [ 54 , 62 ]/NETosis [ 63 , 64 ] was validated. According to previous studies, albumin exhibits the potential to inhibit the histone H4-induced platelet aggregation[ 29 ], suggesting albumin as a therapeutic candidate for managing blood coagulation.…”
Section: Resultsmentioning
confidence: 99%
“…During the formation of ETs resistant to pathogen invasion, MPO may drive chromatin decondensation, a critical step in ET formation [49]. In addition, H4Cit3 is a well-established NET marker [51]. Peptidylarginine deiminase 4 targets histone arginine and monomethylarginine residues for citrullination in a calcium-dependent reaction [52].…”
Section: Discussionmentioning
confidence: 99%